Appropriateness of Liver Biopsy - Thierry Poynard; Vlad Ratziu; Pierre Bedossa (Canadian Journal of Gastroenterology)
This review aims to discuss the appropriateness of liver biopsy in two frequent liver diseases, hepatitis C and alcoholic liver disease. The medical literature, published between 1965 and 1999, was reviewed by using MEDLINE. Only 0.1% of the publications were devoted specifically to the appropriateness of liver biopsy. Not all studies observed a significant agreement among doctors on the decision to use liver biopsy. Therefore, there is a possibility that hepatologists have significant, heterogeneous opinions concerning the appropriateness of liver biopsy. Appropriateness should be evaluated for different techniques such as percutaneous liver biopsy, guided or not by ultrasonography, and the types of needles, automatic or not. The present paper reviews the evaluation of liver biopsy appropriateness in the real world, the adverse events and mortality of liver biopsy, and the appropriateness of liver biopsy in alcoholic liver disease and chronic hepatitis C. The authors conclude that liver biopsy is used extensively, but its appropriateness has not been evaluated perfectly. Therefore, further evaluation of the appropriateness of liver biopsy in the practical algorithm of such diseases is needed.